# tìm x a/(2x ²-3x)=0 b/4+3x ²/x-3 – 2x+2x ²/x-3 + 2x-13/x-3 =0 càn gấp

By Lydia

tìm x
a/(2x ²-3x)=0
b/4+3x ²/x-3 – 2x+2x ²/x-3 + 2x-13/x-3 =0
càn gấp

### 0 bình luận về “tìm x a/(2x ²-3x)=0 b/4+3x ²/x-3 – 2x+2x ²/x-3 + 2x-13/x-3 =0 càn gấp”

1. ngocdiep

a) $2x^2-3x=0$

$⇔x.(2x-3)=0$

$⇔$$$\left[ \begin{array}{l}x=0\\2x-3=0\end{array} \right.$$

$⇔$$$\left[ \begin{array}{l}x=0\\2x=3\end{array} \right.$$

$⇔$$$\left[ \begin{array}{l}x=0\\x=\dfrac{3}{2}\end{array} \right.$$

b) $\dfrac{4+3x^2}{x-3}-\dfrac{2x+2x^2}{x-3}+\dfrac{2x-13}{x-3}=0$

$⇔\dfrac{4+3x^2-2x-2x^2+2x-13}{x-3}=0$

$⇔\dfrac{x^2-9}{x-3}=0$

$⇔\dfrac{(x-3)(x+3)}{x-3}=0$

$⇔x+3=0$

$⇔x=-3$

Trả lời
2. quynhnhu

Đáp án:

a) 2x^2-3x=0

⇒ x.(2x-3)=0

⇒ $$\left[ \begin{array}{l}x=0\\2x-3=0\end{array} \right.$$

⇒$$\left[ \begin{array}{l}x=0\\2x=3\end{array} \right.$$

⇒$$\left[ \begin{array}{l}x=0\\x=\dfrac{3}{2}\end{array} \right.$$

b)(4+3x^2)/(x-3)-(2x+2x^2)/(x-3)+(2x-13)/(x-3)=0

⇒ (4+3x^2-2x-2x^2+2x-13)/(x-3)=0

⇒ (x^2-9)/(x-3)=0

⇒((x-3)(x+3))/(x-3)=0

⇒x+3=0

⇒x=-3

Trả lời